1997
DOI: 10.1046/j.1365-3024.1997.d01-174.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenotype related responsiveness of peripheral blood lymphocytes from Eimeria tenella infected chickens

Abstract: We have previously shown that the proportion of CD8-expressing T cells (CD8bright+ and CD4+ CD8dim+ cells) in the peripheral blood of chickens increases around 8 days after a primary infection with Eimeria tenella oocysts. The increase in the CD8+ eight cells coincides with enhanced responses after in vitro stimulation with parasite antigen. In the study described here, the responsiveness of these day 8 PBL was further characterized by determining their capacity to proliferate and to produce cytokine (IFN-gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The selective elimination of CD8 + cells resulted in the exacerbation of disease as evidenced by increased oocyst shedding after secondary infection with E. tenella or E. acervulina [ 32 ] . It is known that CD4 + cells play an important helper function in protective immune responses, and CD8 + cells act as effector cells in these processes [ 33 ]. Both CD4+ and CD8+ cells are responsible for the IFN-γ production [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selective elimination of CD8 + cells resulted in the exacerbation of disease as evidenced by increased oocyst shedding after secondary infection with E. tenella or E. acervulina [ 32 ] . It is known that CD4 + cells play an important helper function in protective immune responses, and CD8 + cells act as effector cells in these processes [ 33 ]. Both CD4+ and CD8+ cells are responsible for the IFN-γ production [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that CD4 + cells play an important helper function in protective immune responses, and CD8 + cells act as effector cells in these processes [ 33 ]. Both CD4+ and CD8+ cells are responsible for the IFN-γ production [ 33 ]. IFN-γ production is higher in chicks infected with Eimeria species compared with non-infected chicks, and higher levels of IFN-γ coincide with a protective immune response to the infection [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fraction of antigens that produced the highest T-cell proliferation and macrophage-activating activity, when administered as a vaccine, also yielded chickens with the lowest cecal lesion scores after challenge (20).…”
Section: Vaccinationmentioning
confidence: 95%
“…Because T-cell-stimulatory antigens appear to be the most relevant to protective immunity, T-cell proliferation assays (using T cells from recovering chickens) and IFN-␥ production have been used to screen for protective antigens against E. tenella infections (20). The fraction of antigens that produced the highest T-cell proliferation and macrophage-activating activity, when administered as a vaccine, also yielded chickens with the lowest cecal lesion scores after challenge (20).…”
Section: Vaccinationmentioning
confidence: 99%
“…Moreover, Bagot et al [13] have demonstrated the presence of tumor-specific, MHC class I-restricted, cytotoxic CD4 + CD8 dim T cell clones inside cutaneous infiltrates from patients with cutaneous T cell lymphoma. In monkeys, swine and chicken, species that have markedly more abundant circulating CD4 + CD8 dim T cells than humans, the CD4 + CD8 dim subset appears to have both helper and cytotoxic functions [16][17][18]. were stimulated with CMV lysate as described in Sect.…”
Section: Introductionmentioning
confidence: 99%